Adaptation in conflict: are conflict-triggered control adjustments protected in the presence of motivational distractors?. Issue 4 (19th May 2019) - Becker, Daniela; Jostmann, Nils B.; Holland, Rob W.
ABSTRACT: Solving a conflict between two response options in an interference task has been found to increase control in a subsequent conflict situation. The present research examined whether such conflict adaptation persists in the presence of distractors that have motivational relevance and are therefore competing for attentional resources (i.e. they signal opportunities for monetary gains or losses contingent on overall task performance). In an adjusted flanker task, motivational (versus neutral versus no) distractors were presented together with the current trial while the previous trial never included any distractor. Accumulated evidence across three studies showed that motivational distractors reduced the conflict adaptation effect. This was found irrespective of the location at which the distractor occurred (Study 1), and independent of its valence (i.e. reward or loss, Study 2). Study 3 and a merged data analysis ruled out low-level alternative explanations. In line with a dual competition account (Pessoa, L. (2009). How do emotion and motivation direct executive control? Trends in Cognitive Sciences, 13 (4), 160–166. doi:10.1016/j.tics.2009.01.006 ), our results show that conflict adaptation is not fully protected in the presence of motivational distractors. We discuss whether this should be interpreted as a limitation, or as reflecting the flexibility of the control system in dealing with motivationally relevant information.